The Utilisation of Social Science Research in Policy Development and Program Review - Head, Brian; Cherney, Adrian; Boreham, Paul (New Zealand Science Review, 2019)
The aim of this project was to examine research utilisation within public sector agencies in Australia at both state and national levels, focusing on agencies whose responsibilities include human services policies and programs. This project was concerned with examining the processes, practices and circumstances that facilitate and hinder the uptake of academic social research within policy and program contexts. The project was supported by an Australian Research Council (ARC) grant and undertaken in conjunction with nine public sector industry partners. The project involved both surveys and interviews with academic researchers and staff of public sector age.Results suggest that the current processes, practices and circumstances of both academic researchers and policy-makers inhibit the translation and uptake of academic research within public sector policy contexts. Public sector agencies and academic institutions have very different cultures, incentives and expertise. Both policy staff and researchers attest to the need for better processes for research translation and interaction. Agencies may need to be encouraged to build networks with academic researchers; while academic researchers should heed the preferences of policy-makers, by providing summary documents, translating research find-ings into policy relevant results, and generally transmitting research into formats that facilitate policy uptake.